Immunology & Immune System - Palmowski J; Boßlau TK; Ryl L; Krüger K; Reichel T (Dynamic Media Sales Verlag, 2019)
The prevention of infectious diseases is particularly important inathletes who need a good all-seasonhealth status to be optimally prepared for competition. Since the immune system is highly responsive to exercise, periods of intensi ed training induce a transient immune dysfunction. Athletes regularly encounter additional challenges, such as low energy availability, oxidative stress, psychological stress, sleep disruption, long-haul travel, overreaching periods and an imbalance of exercise and recovery. Moreover, exercise training performed in speci c environments, such as high altitude, cold or heat, represents an even higher than usual threat to the immune function. This review summarizes various recommendations which should help to reduce the athletes immune disturbances and the risk of infection.An appropriate management of external and internal exercise loads, adequate recovery, as well as maintaining energy homeostasis by su cient energy, uid, and macronutrient intake is recommended. . e observance of sleep hygiene strategies, general vaccination advice and instructions for exercising in speci c environments is bene cial. Compliance with fundamental hygiene strategies can also reduce pathogen exposure in athletes and thus contribute to maintaining health. It is concludedthat these main strategies of protection against infection should be included in the early education of coaches and young athletes, leading to more professional management of disease prevention. KEY WORDS: Immune System, Exercise, Training, Immune Disturbance, Upper Respiratory Tract Infections